P30-58 Extraction and Evaluation of Latent Representations from Peripheral Blood Smear Images - T. Iwasaka; T. Mizuno; K. Morita; I. Azuma; E. Nakashima; H. Kusuhara (Toxicology Letters, 2025)

P03-12 Network-Based Modeling of Immune Cell Interactions to Elucidate the Mechanisms of Toxicity - I. Azuma; T. Mizuno; H. Kusuhara (Toxicology Letters, 2025)

P12-08 Establishment of a novel and simple drinking water liver injury model for hepatotoxicity research - T. Iwasaka; T. Mizuno; K. Morita; I. Azuma; T. Nakagawa; E. Nakashima; H. Kusuhara (Toxicology Letters, 2024)

Legacy over a thousand years: Canopy soil of old-growth forest fosters rich and unique invertebrate diversity that is slow to recover from human disturbance - Ikuyo Saeki; Sho Hioki; Wakana A. Azuma; Noriyuki Osada; Shigeru Niwa; Aino T. Ota; Hiroaki Ishii (Biological Conservation, 2024)

Interspecific hybridization of fig (Ficus carica L.) and Ficus erecta Thunb., a source of Ceratocystis canker resistance - H. Yakushiji; T. Morita; S. Jikumaru; H. Ikegami; A. Azuma; Y. Koshita (Euphytica, 2012)

Occlusal Disharmony Increases Amyloid-β in the Rat Hippocampus - D. Ekuni; T. Tomofuji; K. Irie; T. Azuma; Y. Endo; K. Kasuyama; M. Morita (NeuroMolecular Medicine, 2011)

Synchronized development of gonad and bioluminescent light organ in a highly sexually dimorphic leiognathid fish, Photoplagios rivulatus - K. Ikejima; M. Wada; K. Kita-Tsukamoto; T. Yamamoto; N. Azuma (Marine Biology, 2008)

Genetic structure of masu salmon ( Oncorhynchus masou ) populations in Hokkaido, northernmost Japan, inferred from mitochondrial DNA variation - S. Kitanishi; K. Edo; T. Yamamoto; N. Azuma; O. Hasegawa; S. Higashi (Journal of Fish Biology, 2007)
Genetic structure of masu salmon Oncorhynchus masou populations in Hokkaido was examined by analysing mtDNA NADH dehydrogenase subunit 5 gene (561 bp) of 382 individuals collected from 12 rivers, in which there were no records of artificial release. Analysis of molecular variance showed that between groups level and between populations within‐group level explained each c. 10% of genetic variance. In neighbour‐joining tree, four populations located in southern Hokkaido were clustered into a single group; however, other populations did not form any clear clusters. Fu’s F S , Tajima’s D and a mismatch distribution test indicated a sudden expansion of population in the entire population of Hokkaido and the northernmost population of Chiraibetsu, which was genetically close to the southern Hokkaido group. The Sea of Japan and southern rivers, including those of southern Hokkaido, seem to have served as refugia for masu salmon during glacial periods, and their dispersal and straying in interglacial periods affected the genetic structure of masu salmon populations in Hokkaido.

Salmon gonadotropes secrete free form alpha (α)-subunit: quantitative analysis by the sandwich cell immunoblot assay - N. Naito; Y. Koide; T. Yada; T. Azuma; H. Kawauchi (Fish Physiology and Biochemistry, 2003)

Floral scent chemistry of mangrove plants - H. Azuma; M. Toyota; Y. Asakawa; T. Takaso; H. Tobe (Journal of Plant Research, 2002)

Internal Distribution of Acid Materials within Snow Crystals - H. Fushimi; T. Kawamura; H. Iida; M. Ochiai; T. Nakajima; Y. Azuma (Water, Air, & Soil Pollution, 2001)

The impact of the CYP2D6 and CYP2C19 genotypes on venlafaxine pharmacokinetics in a Japanese population - T. Fukuda; Y. Nishida; Q. Zhou; I. Yamamoto; S. Kondo; J. Azuma (European Journal of Clinical Pharmacology, 2000)

Circadian variation of the urinary 6β-hydroxycortisol to cortisol ratio that would reflect hepatic CYP3A activity - M. Ohno; I. Yamaguchi; T. Ito; K. Saiki; I. Yamamoto; J. Azuma (European Journal of Clinical Pharmacology, 2000)

Cardiac profile of EGIS-9377, a novel cardiotonic agent as a Ca2+ sensitizer with bradycardiac activity - Y. Hattori; T. Ishitani; F. Tomita; S. Gando; H. Yokoshiki; M. Azuma; O. Kemmotsu; M. Kanno (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

CYP2C19 genotypes and omeprazole metabolism after single and repeated dosing when combined with clarithromycin - Q. Zhou; I. Yamamoto; T. Fukuda; M. Ohno; A. Sumida; J. Azuma (European Journal of Clinical Pharmacology, 1999)

Interaction of citrus juices with pranidipine, a new 1,4-dihydropyridine calcium antagonist, in healthy subjects - K. Hashimoto; T. Shirafuji; H. Sekino; O. Matsuoka; H. Sekino; O. Onnagawa; T. Okamoto; S. Kudo; J. Azuma (European Journal of Clinical Pharmacology, 1998)

The effect of Y-25510 injection on the serum levels of some cytokines in healthy adult volunteers - J. Azuma; M. Ogura; I. Yamamoto; M. Hisadome; T. Fukuda; Y. Ikeda; H. Mori; T. Oka; S. Asano (European Journal of Clinical Pharmacology, 1998)

Analysis of the non-sense mutants of varicella-zoster virus thymidine kinase - T. Suzutani; S. Koyano; M. Saijo; A. Chiba; M. Azuma (Archives of Virology, 1997)

Therapy for oral squamous cell carcinoma by tegafur and streptococcal agent OK-432 in combination with radiotherapy: Association of the therapeutic effect with differentiation and apoptosis in the cancer cells - M. Sato; K. Harada; H. Yoshida; Y. Yura; M. Azuma; H. Iga; T. Bando; H. Kawamata; Y. Takegawa (Apoptosis, 1997)